The Hermes Sdn. Bhd. : logistic (forwarding agent) / Raja Syahrul Izahar Raja Hasan ... [et al.] - Raja Hasan, Raja Syahrul Izahar; Lenin, Mohd Redzuan; Dollah, Mohd Faizie; Mahmud, Shafie (Faculty of Information Management, 2002)
Forwarding agent is a courier-type business. The only thing that courier is a big business while forwarding is a small one. Forwarding agent is the idle an doing transactions between importers especially consignees, the customs department and the port management. Due to the coming AFTA, opening a forwarding agent company is actually grabbing an opportunity. After considering for about some tie we decided to open the office in Westport. It is because the location must be near the port for the tie in doing business can be saved. Considering the AFTA in 2003, we hope to increase the number of our consignees because our income depends on the number of transactions that was assigned by the consignees. We target that at the year 2003, the number of importers will grow. And lastly we hope to do haulage if this business expands rapidly.